Enhancing Support For Senior Citizens: Development And Evaluation of The OSCA Information Management System With Agile Methodology and ISO/IEC 25010 Compliance - Johannah Mae C. Velasquez; Alexander S. Cochanco; Ruth G. Luciano (Journal of Applied Engineering and Technological Science (JAETS), 2023)
The elderly were a member of the vulnerable group which the government supported and assisted in every way possible. To contribute to the support and assistance needed by the elderly who are called senior citizens, this study was conducted. This aims to develop and design a usable, performance-efficient, and functional suitable to the operation and service of the Office of the Senior Citizen Affairs (OSCA), Cabanatuan City office. The System Application Office of the Senior Citizen Affairs Information Management System with Analytics (OSCA-IMSA) was developed using the Agile System Development Life Cycle (SDLC) Model. The agile model has different phases and sub-phases that guarantee the quality and efficient development of the system. Every phase and sub-phases lead to a well-organized, and systematic process of system development. The proponents adopted the ISO/IEC 25010 criteria as an evaluation tool to assess the system's usability, reliability, performance efficiency, functional suitability, security, portability, maintainability, and compatibility. The self-made survey questionnaire was used as the main tool to collect the data from the respondents. Purposive sampling was used to determine the right respondents for the study. The study was composed of two different sets of respondents, the first set was the System Users and the second set was composed of IT Experts. The Office of the Senior Citizen Affairs Information Management System with Analytics (OSCA-IMSA) was evaluated and assessed by the respondents with a result of being highly functional, highly efficient, highly portable, highly maintainable, highly compatible, highly secured, highly reliable, and highly usable. This result indicates that the system passed and conformed to the ISO/IEC 25010 Software Product Quality Standard, hence, is recommended to be deployed at the research locale.